Multifunctional dietary interventions, low-grade inflammation and cardiometabolic profile: a scoping review - Hornero-Ramirez, Hugo; Aubin, Adrien; Michalski, Marie-Caroline; Vinoy, Sophie; Caussy, Cyrielle; Nazare, Julie-Anne (Frontiers in Immunology, 2024)
Growing evidence highlights the significant impact of diet to modify low-grade inflammation closely linked to cardiometabolic profile. Multifunctionnal diets, combining several compounds have been shown to beneficially impact metabolic parameters. This study synthesizes the knowledge on the impact of RCTs combining dietary multifunctional compounds on low-grade inflammation in humans. We investigate whether the effects of dietary multifunctional interventions on inflammatory markers were parallel to alterations of cardiometabolic parameters. We considered both the integrated dietary interventions (ID, i.e. global diets such as Mediterranean, Nordic…) and the dietary interventions based on selected bioactive mix (BM) compounds, in healthy individuals and those at cardiometabolic risk. Out of 221 screened publications, we selected 27 studies: 11 for BM (polyphenols and/or omega-3 fatty acids and/or antioxidants and/or dietary fiber) and 16 for ID (Mediterranean, paleo, Nordic, Dietary Approaches to Stop Hypertension (DASH) diet...). ID studies reflected significant improvements in inflammatory markers (CRP, IL-6, IL-10, IL-1b), concomitantly with beneficial changes in metabolic parameters. In BM studies, pronounced effects on low-grade inflammatory markers were observed, while improvements in metabolic parameters were not consistent. Both types of studies suggested a favorable impact on oxidative stress, a factor closely linked to the inflammatory profile. Our findings showed that multifunctional RCT diets have differential role in managing low-grade inflammation and cardiometabolic health, with a large heterogeneity in explored inflammatory markers. Further research is imperative to elucidate the link between low-grade inflammation and other cardiometabolic risk factors, such as intestinal inflammation or postprandial inflammatory dynamics, aiming to attain a comprehensive understanding of the mechanisms involved in these processes. These future investigations not only have the potential to deepen our insights into the connections among these elements but also pave the way for significant advancements in the prevention and management of conditions related to the cardiovascular and metabolic systems.